Gamer Girls, Gold Farmers, and Activism In Real Life. - Musgrave, Megan (Children's Literature in Education, 2016)
This essay analyzes the graphic novel In Real Life as an example of Cory Doctorow and Jen Wang's intention to raise young people's awareness about gender and economic disparities within the gaming industry. Broadly, In Real Life combats the pervasive cultural anxiety that Jane McGonigal challenges in her book Reality is Broken-namely that young people's growing connection to technology, and specifically to gaming, will cause them to spend their lives 'wasting time, tuning out, and losing out on real life' (2011, p. 11). Specifically, it provides a realistic, accessible example of digital citizenship for twenty-first century youth. The innovative notions of digital citizenship Doctorow and Wang present in the text call for an end to gender and economic marginalization as facilitated by a gaming industry in which many young adults participate. By connecting gaming to activism, In Real Life offers a new avenue by which to use young adult literature to inspire civic engagement on the part of young people. The aim is to show that the imaginary activism depicted in literature not only has the potential to, but is actually designed to engage young people as active users, consumers, and shapers of technology.